(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
This paper presentsfor bringing changes in business environment using business plan calledmultilevel marketing. The paper describes what multi-level marketing is, why itis used, and what its limitations are. As compared to the existing system, theMLM system has been found to be much more memory, resource and time efficient.The system is simple to maintain. The concept of Multilevel Marketing or networkmarketing is a method of product distribution. The products are moved throughindependent distributors. The distributors are given an opportunity tointroduce other distributors to the business. Instead of calling massive mediaadvertising and sales promotion cost, the savings are passed on to distributorconsumers. The paper describes the better performance of distributors inmultilevel marketing in business environment.